ROBUST OPTIMAL DESIGN OF MULTIPLE RESPONSE OF FLEXIBLE HINGE BASED ON THE TAGUCHI AND SATISFACTION FUNCTION METHOD - WU JianJun; HUANG YuLin; XIE ZhouWei; LIANG LunHai; LIANG Kai (Jixie qiangdu)
It is difficult to optimize flexibility robustness because the robust optimization of multiple response for cell injection 3 RRR compliant parallel micro motion platform flexible parts are existed"under"deformation or"over"deformation. a new method is proposed to solve the robust optimization of multiple response which combine the Taguchi method and satisfaction function. Firstly,the hinge motion model compliance of micro-platform multi-directional is established and the response surface test design based on this model. Secondly,the taguchi method is introduced to analyze the stability of multiple response. Finally,the satisfaction function is used to taken the issues of multiple response optimization into maximal value of overall satisfaction and get the robust optimization design plan under the restriction of multiple response flexibility. Examples show that this method can provide a new solution for robust optimal design of the multiple response of flexible hinge.